AZD1080, a novel GSK3 inhibitor, rescues synaptic plasticity deficits in rodent brain and exhibits peripheral target engagement in humans. (11th March 2013) - Georgievska, Biljana; Sandin, Johan; Doherty, James; Mörtberg, Anette; Neelissen, Jan; Andersson, Anita; Gruber, Susanne; Nilsson, Yvonne; Schött, Pär; Arvidsson, Per I.; Hellberg, Sven; Osswald, Gunilla; et al.
Abstract Abnormal tau phosphorylation resulting in detachment of tau from microtubules and aggregation are critical events in neuronal dysfunction, degeneration, and neurofibrillary pathology seen in Alzheimer's disease. Glycogen synthase kinase‐3β (GSK3β) is a key target for drug discovery in the treatment of Alzheimer's disease and related tauopathies because of its potential to abnormally phosphorylate proteins and contribute to synaptic degeneration. We report the discovery of AZD1080, a potent and selective GSK3 inhibitor that demonstrates peripheral target engagement in Phase 1 clinical studies. AZD1080 inhibits tau phosphorylation in cells expressing human tau and in intact rat brain. Interestingly, subchronic but not acute administration with AZD1080 reverses MK‐801‐induced deficits, measured by long‐term potentiation in hippocampal slices and in a cognitive test in mice, suggesting that reversal of synaptic plasticity deficits in dysfunctional systems requires longer term modifications of proteins downstream of GSK3β signaling. The inhibitory pattern on tau phosphorylation reveals a prolonged pharmacodynamic effect predicting less frequent dosing in humans. Consistent with the preclinical data, in multiple ascending dose studies in healthy volunteers, a prolonged suppression of glycogen synthase activity was observed in blood mononuclear cells providing evidence of peripheral target engagement with a selective GSK3 inhibitor in humans.